Male Sex Is Associated With Higher Rates of Liver‐Related Mortality in Primary Biliary Cholangitis and Cirrhosis. Issue 2 (26th May 2021) - John, Binu V.; Aitcheson, Gabriella; Schwartz, Kaley B.; Khakoo, Nidah S.; Dahman, Bassam; Deng, Yangyang; Goldberg, David; Martin, Paul; Taddei, Tamar H.; Levy, Cynthia; Kaplan, David E.
Abstract : Background and Aims: The impact of sex on the postcirrhosis progression of primary biliary cholangitis (PBC) has not been well defined. Prior studies have suggested that men have worse outcomes but present at more advanced stages of fibrosis than women. This observation, however, has been limited by small numbers of men and even fewer patients with cirrhosis. Approach and Results: We investigated the association of sex with the development of all‐cause and liver‐related mortality or transplantation, decompensation, and hepatocellular carcinoma (HCC), using competing‐risk time‐updating Cox proportional hazards models in a large cohort of predominantly male patients with PBC cirrhosis assembled from the Veterans Health Administration. In a cohort of 532 participants (418 male) with PBC‐related cirrhosis with a total follow‐up of 3, 231.6 person‐years (PY) from diagnosis of compensated cirrhosis, male participants had a higher unadjusted rates of death or transplantation (8.5 vs. 3.8 per 100 PY; P  < 0.0001), liver‐related death or transplantation (5.5 vs. 2.7 per 100 PY; P  < 0.0001), decompensation (5.5 vs. 4.0 per 100 PY; P  = 0.002), and HCC (0.9 vs. 0.3 per 100 PY; P  < 0.0001). After adjusting for confounders,  male sex was associated with a higher risk of death or transplantation (adjusted hazard ratio, 1.80; 95% CI, 1.01‐3.19; P  = 0.046), and liver‐related death or transplantation (subhazard ratio, 2.17; 95% CI, 1.15‐4.08; P  = 0.02). A sensitivity analysis that defined ursodeoxycholic acid response as normalization of alkaline phosphatase and total bilirubin revealed similar findings. Conclusions: In patients with PBC and well‐compensated cirrhosis, male sex is associated with a higher risk of both death and liver‐related death or transplantation.